2004
DOI: 10.1021/ef034087w
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Formation of CO2 Hydrate via a Kenics-Type Static Mixer

Abstract: Formation of CO2 hydrate using a Kenics-type static mixer was studied experimentally. The flows of liquid CO2 and water were mixed in the static mixer, and CO2 hydrate was formed continuously from the two-phase flow. The patterns of hydrate formation were found to be dependent on the flow velocities of liquid CO2 and water. The flow of agglomerated hydrate chunks in water occurred under relatively CO2-rich conditions, while dispersed flow of tiny particles of CO2 hydrate with small liquid CO2 drops was observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 16 publications
0
29
0
Order By: Relevance
“…(4) Mechanical agitation: Experiments show that stirring, shaking, or shocking can trigger nucleation in a supersaturated fluid [Mullin, 2001;Mullin and Raven, 1962;Skovborg et al, 1993;Young, 1911;Young and Cross, 1911]. Similarly, mechanical stimulation facilitates ice nucleation and gas hydrate formation [Barrer and Edge, 1967;Skovborg et al, 1993;Sloan and Fleyfel, 1991;Tajima et al, 2004]. Experimental results for other systems show that the nucleation rate and the morphology of precipitates are affected by stirring conditions and rate [Akkermans et al, 2006;Liang et al, 2004;Ting and McCabe, 1934].…”
Section: Previous Studiesmentioning
confidence: 99%
“…(4) Mechanical agitation: Experiments show that stirring, shaking, or shocking can trigger nucleation in a supersaturated fluid [Mullin, 2001;Mullin and Raven, 1962;Skovborg et al, 1993;Young, 1911;Young and Cross, 1911]. Similarly, mechanical stimulation facilitates ice nucleation and gas hydrate formation [Barrer and Edge, 1967;Skovborg et al, 1993;Sloan and Fleyfel, 1991;Tajima et al, 2004]. Experimental results for other systems show that the nucleation rate and the morphology of precipitates are affected by stirring conditions and rate [Akkermans et al, 2006;Liang et al, 2004;Ting and McCabe, 1934].…”
Section: Previous Studiesmentioning
confidence: 99%
“…Static mixers are motionless mixing devices with fixed "mixing elements" arranged in a straight pipe. The Kenics static mixer experiments demonstrated that two fluids (drop/bubble and water) are efficiently agitated with the mixing elements and are subsequently converted to hydrate formed on the drop/bubble surface at specific temperature and pressure conditions (Tajima et al, 2004(Tajima et al, , 2007. Several structures of mixing element are designed for efficient agitation/mixing of fluids more than one.…”
Section: Semi-batch Flow Reactor With Static Mixermentioning
confidence: 99%
“…Fig. 9 shows the speculated mechanisms for hydrate formation in static mixing-type flow reactor according to experimental results (Tajima et al, 2004(Tajima et al, , 2005(Tajima et al, , 2011b. The r d , r f , and r s are rates of target gas dissociation to water, target gas hydrate nucleation and growth, and target gas hydrate particle/film shedding, respectively.…”
Section: Feasible Mechanism Of Hydrate Formation In Static Mixing-typmentioning
confidence: 99%
“…Some examples of the application of static mixers for dispersive mixing of gaseous phase into liquid phase are ozonation processes in waste water treatment process, scrubbing ammonia or cyanides with water and hydrogenation of vegetable oils [1,6,7,20]. Tajima and his colleagues [21][22][23] analytically and experimentally elucidated the effects of flow division, flow reversal and secondary flow induced by the Kenics static mixer on the formation of CO2 hydrate. The liquefied CO2 was transported through a pipeline and mixed with seawater in a KSM at a depth of 500−1 000 m then released into the ocean.…”
Section: Introductionmentioning
confidence: 99%